Aetiology and pathogenesis of bone marrow lesions and osteonecrosis of the knee. Issue 5 (31st May 2016) - Marcacci, Maurilio; Andriolo, Luca; Kon, Elizaveta; Shabshin, Nogah; Filardo, Giuseppe
Abstract : Bone marrow lesions (BML) of the knee are a frequent MRI finding, present in many different pathologies including trauma, post-cartilage surgery, osteoarthritis, transient BML syndromes, spontaneous insufficiency fractures, and true osteonecrosis. Osteonecrosis (ON) is in turn divided into spontaneous osteonecrosis (SONK), which is considered to be correlated to subchondral insufficiency fractures (SIFK), and avascular necrosis (AVN) which is mainly ascribable to ischaemic events. Every condition has a MRI pattern, a different clinical presentation, and specific histological features which are important in the differential diagnosis. The current evidence supports an overall correlation between BML and patient symptoms, although literature findings are variable, and very little is known about the natural history and the progression of these lesions. A full understanding of BML will be mandatory in the future to better address the different pathologies and develop appropriately-targeted treatments. Cite this article: Marcacci M, Andriolo L, Kon E, Shabshin N, Filardo G. Aetiology and pathogenesis of bone marrow lesions and osteonecrosis of the knee. EFORT Open Rev 2016;1:219-224. DOI: 10.1302/2058-5241.1.000044.